Recent advances in developing modified electrode interface for sensing tartrazine in real samples: a brief review - Namratha Anaji; Gururaj Kudur Jayaprakash; Praveen Naik; Girish Tigri; Sathish Reddy (Journal of Electrochemical Science and Engineering)
Many businesses, including sectors of food, textile, pharmaceuticals, and cosmetics, employ tartrazine or other synthetic dyes. These dyes cause severe health effects if used or consumed frequently. Hence, it is important to be aware and take precautions before their use. Up to now, researchers have introduced many electrochemical methods for determination of tartrazine. Among them, voltammetric methods were developed, mostly using effective and selective electrodes with modifiers to accurately sense tartrazine in baking products such as soft drinks, candy, jelly, and other beverages. In this review, we have covered several works on carbon based, graphite based and gold electrodes, that have been offered for tartrazine detection with good recovery rates and detection limits. These works may aid in future research and development toward more accurate tartrazine detection.